Privatisations as price reforms: Evaluating consumers' welfare changes in the UK - Rinaldo Brau; Massimo Florio (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper analyses the effects on consumers' welfare of the privatisation policy carried out in the UK since 1979. The approach we follow sees the privatisation of a State owned enterprise within the broader framework of the "policy reform" theory (Drèze and Stern, 1990). By adopting this perspective, the change in consumers' welfare "with" and "without" privatisations can be studied by appropriate welfare measures. We claim that an advantage of our approach is that of being able to provide the required welfare assessment in a simplified way by means of a limited set of information. In particular, we show that a series of welfare measures only based on aggregate information can be used once one becomes ready to accept the use of first and second order approximations and a few "reasonable" assumptions on the shape of demand functions. These welfare measures are subsequently used for the evaluation of the welfare effects related to price variations in seven British privatised public utilities. We conclude that the contribution to consumers' welfare of the privatisation policy in the UK, when compared to the huge transfers involved in the process, has been rather modest
Keywords: L33; D6; D12; 330; Privatisation; welfare measurement; Privatisierung; Preis; Wohlfahrtsanalyse; Theorie; Großbritannien